Hann, Ruby. Interview about her life experiences as a volunteer. - Hannon, Sarah. (2016)
Oral interview with Ruby Hann, conducted by Sarah Hannon and Terra Barrett. Interview includes a short life history and a discussion of her involvement with volunteer work; volunteering at the Mews Centre; Ivy, a volunteer who inspired Ruby; what she loves about volunteering; helping veterans; advice for anyone who wants to start volunteering;